Teacher Readiness in Implementing the Independent Curriculum in Elementary Schools: Challenges and Strategies - Ritme, Ritme; Adam, Adam; Deluma, Ridwan (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
This study aims to analyze teacher readiness in implementing the Independent Curriculum in elementary schools, as well as provide recommendations for improving learning practices and educational policies. Using a qualitative method with a multi-case study approach at SDN 6 and SDN 7 Kodeoha, data were collected through interviews, classroom observations, and document analysis. The results show that teachers have understood the basic concepts of the Independent Curriculum, but still experience challenges in its implementation, such as gaps in student abilities, limited teaching materials, and resistance to new learning methods. Limited technological infrastructure and low parental involvement are also obstacles. This study recommends practice-based training for teachers, improving learning facilities, and strengthening communication between schools and parents. These findings are expected to be the basis for developing a more effective implementation strategy for the Independent Curriculum at the elementary school level .